Induction of cell death in pancreatic ductal adenocarcinoma by indirubin 3′-oxime and 5-methoxyindirubin 3′-oxime in vitro and in vivo. (1st July 2017) - Sano, Makoto; Ichimaru, Yoshimi; Kurita, Masahiro; Hayashi, Emiko; Homma, Taku; Saito, Hiroaki; Masuda, Shinobu; Nemoto, Norimichi; Hemmi, Akihiro; Suzuki, Takashi; Miyairi, Shinichi; Hao, Hiroyuki
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with a poor prognosis. To identify potential effective therapeutic drugs for PDAC, we established a screening system based on spheroid formation using 170#3 mouse PDAC cells with or without fibroblasts. We found that indirubin 3′-oxime (Indox) and 5-methoxyindirubin 3′-oxime (5MeOIndox) inhibited PDAC cell proliferation. Furthermore, PDAC xenograft growth was also inhibited in BALB/c nu/nu mice after administration of Indox and 5MeOIndox. Both phosphorylated CDK1 and cyclin B1 levels in 170#3 cells were significantly reduced by treatment with Indox and 5MeOIndox in vitro and in vivo . Cell cycle analysis revealed that 5MeOIndox, but not Indox, induced G2/M arrest. Annexin V–propidium iodide double-staining analysis demonstrated that Indox induced abundant non-apoptotic cell death of 170#3 cells, while 5MeOIndox predominantly induced early apoptosis, indicating that the cytotoxicity of 5MeOIndox is lower than that of Indox. These results suggest that one mechanism of 5MeOIndox is to induce G2/M arrest of PDAC cells via inhibition of CDK1/cyclin B1 levels, thereby leading to apoptosis. Our findings suggest 5MeOIndox as a potential useful anticancer agent in PDAC. Highlights: Indox and 5MeOIndox inhibit proliferation of PDAC. Indox and 5MeOIndox inhibit p-CDK1/cyclin B1. 5MeOIndox induces G2/M arrest and apoptosis.